Knowledge and Practices Regarding Usage of Biological Safety Cabinets. (March 2017) - Miring'u, Gabriel; Bundi, Martin; Muriithi, Betty Kathomi; Apondi, Ernest Wandera; Galata, Amina Ababa; Kathiiko, Cyrus Njogu; Odoyo, Eric Omondi; Guyo, Sora Huka; Ongubo, Obed Nyang'ate; Ouko, John Odhiambo; Karama, Mohammad; Shah, Mohammad; et al.
When properly used and adequately maintained, a biological safety cabinet (BSC) provides protection to the laboratory worker, the products, and the environment. Knowledge about proper use of the BSC is therefore important. This study evaluated BSC usage knowledge and practices and the effect of prior experience on training outcomes. Thirteen participants randomly selected from research centers were evaluated through a structured questionnaire covering biosafety considerations involved in using a BSC as per the World Health Organization's Laboratory Biosafety Manual, third edition. The questionnaire was administered before and after the training. Training was conducted using the NUITM-KEMRI biosafety training program, enhanced to include more modules on BSCs. Differences in the participants' knowledge and practices regarding BSC usage were observed. After training, the participants were able to give correct responses. Furthermore, participants who had fewer years of experience showed the greatest improvement. Results indicate the need for proper training of laboratory workers early in their careers, coupled with close supervision, mentorship, and regular refresher training.